Glutathione S-Transferase Mu-3 Predicts a Better Prognosis and Inhibits Malignant Behavior and Glycolysis in Pancreatic Cancer - Wang, Shunda; Yang, Jinshou; Ding, Cheng; Li, Junjie; You, Lei; Dai, Menghua; Zhao, Yupei (Frontiers in Oncology, 2020)
Background: Pancreatic cancer (PC) is a lethal malignancy with an extremely unfavorable 5-year survival rate and a high mortality rate. Glutathione S-transferase mu-3 (GSTM3) has been shown to exert different functions in the progression and development of various cancers, except for PC. This study aimed to explore the role of GSTM3 in the malignant behavior and metabolic aspects of PC, its clinical significance, and its possible molecular mechanism in pancreatic cancer. Methods: Tumor microarrays of pancreatic ductal adenocarcinoma (PDAC) were used to evaluate the clinicopathological variables and GSTM3 expression by immunohistochemical staining. Kaplan–Meier survival and Cox regression analyses were further performed to assess the prognosis. The effect of GSTM3 on PC aggressiveness was detected using overexpressing and silencing transfection methods. Western blot, RT-qPCR, CCK-8, and cell cycle assay were applied to evaluate the expression level and proliferation. A xenograft animal model was assessed. Reactive oxygen species (ROS) were measured using the laser confocal scanner and glycolysis was detected using an Agilent Seahorse kit. RNA sequencing was used to assess the underlying mechanism and the signaling pathway involved. Results: GSTM3 was relatively poorly expressed in PDAC tissues compared to para-tumoral tissues and a high level of GSTM3 indicated good overall survival. Functionally, overexpression of GSTM3 could significantly inhibit cell proliferation by delaying the G0/G1 transition, whereas the opposite results were found in the GSTM3 downregulation group. In addition, xenograft animal models further confirmed the effect on proliferation. Moreover, silencing of GSTM3 induced ROS accumulation and promoted glycolysis in PC, indicating its tumor suppressive effect, and vice versa when GSTM3 was upregulated. Finally, RNA sequencing results demonstrated that GSTM3 facilitates anti-tumorigenicity partly via the JAK-STAT signaling pathway in PC. Conclusion: GSTM3 inhibited tumor progression and altered the metabolic pattern in PC. This may be a potential predictive biomarker in PC and a prospective therapeutic target.